Pengaruh Media pada Karakter Biokimia dan Keberhasilan Pencangkokan Tanaman Teh (Camellia sinensis L. (O.) Kuntze) pada Klon TRI 2025 - Ika Betty Widyastuti; Prapto Yudono; Eka Tarwaca Susila Putra (Jurnal Ilmu Pertanian Indonesia, 2021)
The large number of old, damaged, or dead tea plants cause the plant population per hectare to be low that eventually decreases the productivity. Propagation using the transplantation technique is used for embroidery because it has the advantage of a shorter immature plant period and higher seed size so that it can compensate for the surrounding plants but the weakness of transplantation is low success rate. This study aims to 1) determine the morphological changes of root transplantation and biochemistry on TRI 2025 clone transplantation using cocopeat, husk charcoal, and moss, 2) determine the success rate of transplantation in each medium. This research was conducted in August 2018–January 2019 at the Pagilaran production garden, PT. Pagilaran, Batang, Central Java. Field experiments were prepared using a single factor Completely Randomized Environment Design (CRD). The factors tested were the type of transplantation media, namely the media of husk charcoal, cocopeat, and moss. Observations were made on transplantation root morphology, levels of glucose, sucrose, and total sugar in the transplanted stem bark and the concentration of auxin, gibberellin, and cytokinin in the transplant roots. The data obtained were then analyzed using variance and if there was a significant difference between treatments, the Duncan multiple distance test (DMRT) was continued at the 95% confidence level. The results showed that the type of media had no significant effect on the ability to form glucose, sucrose, and total sugar in the bark. The development of root morphology of cocopeat media was seen to be the highest. The ratio of cytokinin/auxin in cocopeat was the lowest but the highest levels of cytokinin and auxin were found in moss, while cocopeat had the highest level of gibberellin. The highest transplanting success rate was found in moss medium with 58.33%, cocopeat and husk charcoal media had the same success rate, namely 41.60%. Keywords: transplantation, biochemistry, media, success, TRI 2025